Consumer loan contract (analytical study in terms of concept and features) - Hassan Badr, Mohamed; Omar Mohamed, Dr.Alaa (Basra studies journal, 2022)
The consumer loan is one of the types of loans granted by banks usually as its purpose is to meet the individual’s personal needs. In the contractual relationship, this contract has a number of characteristics, the most prominent of which is the commercial nature of this contract in addition to the admissible nature. The consumer loan contract is one of the contracts of compliance because the borrower accepts the conditions set by the lending institution without any discussion of the terms of this contract. What distinguishes this contract from the ordinary loan contract that Organized by most of the civil laws, including the Iraqi civil law, as the borrower in the consumer loan contract enjoys the protection stipulated in the consumer protection laws, and there is a link between the loan contract and the funded operation, as the loan contract cannot be concluded in isolation from the funded operation, in addition to that, the benefits imposed from Before the institution granting the loan exceeds the percentages specified in the Civil Code.